Medical tourism: Medical dream or nightmare? - Banerjee, Indrajit; Robinson, Jared; Dev, Kritika; Singh, Ashok Pratap (Journal of Advances in Internal Medicine, 2024)
Medical tourism is an act of a foreign national traveling across international borders to undergo a particular medical procedure. India, Malaysia, Turkey, Singapore, and Thailand have established themselves as prominent destinations in the medical tourism industry, while Canada and the United Kingdom are commonly sought-after source countries for medical travelers. The medical tourism sector offers a range of benefits and drawbacks for citizens of both the source country and the destination country. Traveling long distances for medical treatment presents inherent risks such as complications during travel and exposure to unfamiliar environments. For instance, patients may face an increased risk of developing deep vein thrombosis (DVTs) due to prolonged periods of immobility during flights or other modes of transportation. The most popular desired procedures for medical tourists include elective cosmetic surgery, dental procedures, organ transplants, cardiac surgery, and orthopaedic surgery.Medical tourism is double-edged in nature and can be both beneficial to the health system and the recipient thereof. It is however clear that various international legal and regulatory frameworks are necessitated to both protect the interests of the medical tourist and the treating medical body. There is no question that medical tourism will continue to rise in popularity, it is however prudent that potential medical tourists do their due diligence into the potential destination for their treatment of choice to better nullify the likelihood of a medical misadventure occurring.